2010
DOI: 10.1111/j.1744-9987.2010.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Evaluated by Multi‐Frequency Bioimpedance Is Not Associated With Quality of Life or Depressive Symptoms in Hemodialysis Patients

Abstract: Hemodialysis therapy significantly impacts on patients' physical, psychological, and social performances. Such reduced quality of life depends on several factors, such as malnutrition, depression, and metabolic derangements. This study aims to evaluate the current nutritional status, quality of life and depressive symptoms, and determine the possible relationships with other risk factors for poor outcomes, in stable hemodialysis patients. This was a single-center, cross-sectional study that enrolled 59 adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…General health and average health SF36 scores were greater for those men with a normal ALM index. On univariate analysis, we found no associations with fat mass index and depression, anxiety or general health scores, in keeping with a previous report that measured total bodyfat . On the other hand, patients with reduced ALM index had higher BDI‐II scores, and higher HADS scores, showing an association between reduced appendicular muscle and increased depression and anxiety.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…General health and average health SF36 scores were greater for those men with a normal ALM index. On univariate analysis, we found no associations with fat mass index and depression, anxiety or general health scores, in keeping with a previous report that measured total bodyfat . On the other hand, patients with reduced ALM index had higher BDI‐II scores, and higher HADS scores, showing an association between reduced appendicular muscle and increased depression and anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…On univariate analysis, we found no associations with fat mass index and depression, anxiety or general health scores, in keeping with a previous report that measured total bodyfat. 34 On the other hand, patients with reduced ALM index had higher BDI-II scores, and higher HADS scores, showing an association between reduced appendicular muscle and increased depression and anxiety. Whereas higher SF36 self-reported scores, suggestive of better general health were associated with greater appendicular muscle mass.…”
Section: Discussionmentioning
confidence: 94%
“…The results of studies assessing the association between depression and malnutrition showed variable results [27][28][29]. These studies most commonly used BDI as screening tool for depression.…”
Section: Discussionmentioning
confidence: 97%
“…Poor exercise tolerance and muscle weakness may limit daily activity, again causing poor QoL (Hsieh et al, 2007;Sakkas et al, 2003). However, Barros et al (2011) suggested there was no association of nutritional status with malnutrition-inflammation, QoL, or depressive symptoms. There is still debate about whether patients' QoL can be directly correlated to malnutrition-inflammation markers.…”
Section: Decreased Quality Of Life (Qol)mentioning
confidence: 99%